2020
DOI: 10.21511/imfi.17(4).2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the application of IFRS and the accounting information quality in Jordan

Abstract: The study aimed to find out the relationship between the application of international financial reporting standards (IFRS) and the accounting information quality (AIQ) in Jordan. The research data was collected from 59 industrial companies listed on the Amman Stock Exchange (ASE) between 2010 and 2018. Panel data was used to measure an independent variable (the application of IFRS), and a questionnaire (a 5-point Likert scale) was applied to measure a dependent variable (AIQ). Multiple regression was used to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This study used panel data analysis. Multiple regression was used to test hypotheses (Alawaqleh, 2020). The measure used for financial performance is the ROI ratio, while the first independent variable (Working Capital Management) was measured by using deposits to total assets, cash to assets, asset turnover, net loans to total assets, and current assets to total assets.…”
Section: Data Hypotheses and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used panel data analysis. Multiple regression was used to test hypotheses (Alawaqleh, 2020). The measure used for financial performance is the ROI ratio, while the first independent variable (Working Capital Management) was measured by using deposits to total assets, cash to assets, asset turnover, net loans to total assets, and current assets to total assets.…”
Section: Data Hypotheses and Methodsmentioning
confidence: 99%
“…Furthermore, the Deloof and Jegers (1996) reveals that the assessed profitability, which includes total operating income and an average of the accounts, has a good quality and competency relationship. Therefore, Boisjoly (2009) confirmed that the account management has been http://dx.doi.org/10.21511/bbs.16 (4).2021. 19 stressed on many companies for over 15 years.…”
Section: Working Capital Managementmentioning
confidence: 96%